CSS and documents - Meyer, Eric A. (O'Reilly Media, 2012)
Cascading Style Sheets (CSS) is a powerful tool that transforms the presentation of a document or a collection of documents, and it's spread to nearly every corner of the Web-as well as many non-web environments. In this free introduction to Cascade Style Sheets, you'll learn how CSS makes it possible for you to completely change the way document elements are presented by a user agent. You'll discover the origins of this specification and how CSS styles work with HTML. Learn how you can choose style sheets based on the features of a given media type, including desktop screens, web-enabled ph.